Real-world evidence for an association of vitamin D supplementation with atherosclerotic cardiovascular disease in the UK Biobank - Sha, Sha; Xie, Ruijie; Gwenzi, Tafirenyika; Wang, Youqing; Brenner, Hermann; Schöttker, Ben (Clinical nutrition, 2025)
Background - Atherosclerotic cardiovascular disease (ASCVD) remains a substantial healthcare burden. The Australian D-Health trial recently showed potential efficacy of vitamin D supplementation (VDS) in reducing major ASCVD events. Whether the efficacy could be translated into real-world effectiveness is unclear. - Methods - Leveraging data from the UK Biobank, we used Cox regression with competing risk of all-cause mortality to assess the association of self-reported regular VDS (83.3 % from over-the-counter) and serum 25-hydroxyvitamin D (25[OH]D) levels with ASCVD as a composite endpoint and as separate endpoints including ischemic heart disease (IHD), cerebrovascular disease, peripheral arterial disease, and atherosclerotic disease. - Results - Among 409,822 study participants aged 40-69 years, 20.7 % were vitamin D deficient (25[OH]D < 30 nmol/L) and 34.4 % were vitamin D insufficient (25[OH]D 30-<50 nmol/L). Regular VDS was reported by 4.3 % of the study participants. During the follow-up of 15.9 years, 11.6 % of participants developed ASCVD. Compared to vitamin D sufficiency, vitamin D deficiency was associated with a significantly increased risk of the total ASCVD (hazard ratio [95 % confidence interval]: 1.10 [1.07-1.13]) and all separate ASCVD endpoints in the fully adjusted model with 48 covariates. Consistently, compared to non-users, VDS was associated with a reduced total ASCVD risk in the model fully adjusted for the 50 covariates (0.94[0.90-0.98]). Regarding the individual ASCVD disorders, VDS was associated with reduced IHD risk (0.90[0.86-0.96]). - Conclusion - Self-reported regular VDS and being vitamin D sufficient were both associated with reduced ASCVD risk in real-world settings. For people with low 25(OH)D levels, regular VDS may be a beneficial strategy for ASCVD prevention.
Online verfügbar: 16. April 2025, Artikelversion: 22. April 2025
Gesehen am 20.10.2025